Cognition Assessment Technologies on Deaf People - Coral I. Guerrero-Arenas; Fernando Uristy Osornio-García (Journal of Cognition, 2023)
In recent years there has been a growing interest in research about the different ways of processing and consolidating cognition in deaf people. It is known that hearing loss can lead to differences in some executive functions like control inhibitory or working memory. This literature review describes executive functions in deaf people and how they could be evaluated through technological devices complementing traditional assessments, like neuropsychological batteries. We identified biometric devices, digital and physical interfaces, and software from the literature, whose goal is to design or adapt technology to assess some cognition domains in several ways. The results of the review suggest the need to understand the cognitive phenomenon that significantly impacts the context of deaf people; moreover, it becomes relevant as a line of research in the Cognitive Science of Hearing. Using technologies to measure them and gain a better understanding of cognition in deaf people may provide possibilities for designing or adapting targeted educational or therapeutic strategies.